RESPONSIVITAS DINAS PENANAMAN MODAL PELAYANAN TERPADU SATU PINTU DAN TENAGA KERJA KOTA BATU TERHADAP TINGGINYA TINGKAT PENGANGGURAN DI KOTA WISATA BATU - Retno Wulan Sekarsari; Maulidina Ainur Rosida (JPSI (Journal of Public Sector Innovations), 2019)
This research aims to learn about the causes and impacts of high unemployment rate in Batu City as well as efforts or responses of the Municipal to overcome this issue. The high unemployment rate in Batu City is caused by several factors, namely: low-level of education, lack of skills, ineffective distribution of information on job market for job seekers, relatively low EQ level, lack of socialization on workforce, the general mindset in obtaining jobs, laziness and dependency to others. On the other hand, the high unemployment rate also affects the society in the forms of psychological burden, political and social instability, omission of individual skills, livelihood and income. To reduce the rate of unemployment, there must be efforts and responses from the Municipal, via the Office of Integrated Investment Services and Workforce of the Batu Municipal, to tackle this issue of high unemployment rate in Batu City, such as: planning and organizing œWork Skill Training and Development Activity for Workforce and Society by the Office of Integrated Investment Services and Workforce, establishing cooperation between the Social Issues and Workforce Office and the Industry and Trade Office, organizing Inter-District and Local InterWork Workforce Placement Service Development, Motivation and Management of Informal Sector Entrepreneusrship, and job fairs organized by the Social and Workforce Office of Batu City